2021
DOI: 10.31235/osf.io/ns2te
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loneliness in young people: A multilevel exploration of social ecological influences and geographic variation

Abstract: Background: Loneliness is a growing public health concern, yet little is known about loneliness in young people. The current study aimed to identify social ecological factors related to loneliness and examine the extent to which geographic region accounts for differences in loneliness.Methods: The data come from a cross-sectional sample of 6503 young people living in the United Kingdom. Loneliness was measured using the UCLA 3-item scale. Bivariate analyses were used to test associations between each predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…We also found evidence of wellbeing inequalities varying across neighbourhoods (sex, gender, and sexuality inequalities in both life satisfaction and internalising symptoms). A recent UK study, albeit one involving substantially bigger clusters (local areas), found similar evidence for loneliness among older adolescents (aged [16][17][18][19][20][21][22][23][24] with regard to sex and sexual orientation inequalities [39]. Evidence that wellbeing disadvantage among minority groups may be affected by where young people live provokes a call for more nuanced responses that identify the neighbourhoods with increased vulnerability and inequality.…”
Section: Discussionmentioning
confidence: 99%
“…We also found evidence of wellbeing inequalities varying across neighbourhoods (sex, gender, and sexuality inequalities in both life satisfaction and internalising symptoms). A recent UK study, albeit one involving substantially bigger clusters (local areas), found similar evidence for loneliness among older adolescents (aged [16][17][18][19][20][21][22][23][24] with regard to sex and sexual orientation inequalities [39]. Evidence that wellbeing disadvantage among minority groups may be affected by where young people live provokes a call for more nuanced responses that identify the neighbourhoods with increased vulnerability and inequality.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness and social isolation during residency have detrimental consequences on residents' physical health and quality of life, as well as patient care quality and safety [5]. Furthermore, young adults have been at a higher risk of loneliness than middle-aged adults or older individuals during the COVID-19 pandemic [3]. However, no study has explored the risk factors of loneliness and social isolation in medical residents who are commonly young adults.…”
Section: Discussionmentioning
confidence: 99%
“…Loneliness and social isolation are conceptually related, and are commonly explored together. The prevalence of loneliness in the general population has ranged from 10% to 27% in the United States, Europe, and Japan [2,3]. A cross-sectional study in Germany revealed that approximately 5.4% of adults aged 18-39 years were socially isolated [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, our findings suggest that loneliness is a crucial lever to improving the mental health of adolescents. Research demonstrates that risk factors for adolescent loneliness include, though are not limited to: experiencing social transitions, for example, moving from primary school to secondary school, or starting university, (Siva, 2020;Sundqvist & Hemberg, 2021); low socioeconomic position (Madsen et al, 2019;Varga et al, 2014); having a disability (Maes et al, 2017;ONS, 2019); or being of minority sexual orientation (Gorczynski & Fasoli, 2021;Marquez et al, 2021). Therefore, it may be particularly critical to develop interventions to tackle loneliness and foster meaningful social connections among these groups.…”
Section: Between-school Variation In Mental Health and Differing Effe...mentioning
confidence: 99%